IMAGING OF MENINGIOMA - Duma Ratna Sari Nasution; Ahmad Brata Rosa; Robert P Sinurat; Sanggam B Hutagalung (Buletin Farmatera, 2020)
Meningioma is one of the tumor in the brains that is extra-axial, which means it is not originated from  the brain cell. We report a case of a 60-year-old female, that was admitted to the emergency room (ER) of a secondary referral hospital, due to sudden weakness of upper and lower right extremities since 2 days prior. She had been experiencing a feeling of fullness in the left frontal head since the previous 3 months, along with some headache. She admitted to have had diabetes for the last 2 years. She also reported family history of brain tumor. Neurosurgeon has diagnosed the tumor as a meningioma with differential diagnose a metastatic tumor. A non contrast CT scan has found a meningioma. After being diagnosed, the patient underwent a craniotomy to remove the tumor. The histopathology finding confirmed the diagnosis of meningioma (WHO Grade I). Meningiomas are mostly hyperattenuating to surrounding brain parenchyma, while roughly one fourth are isodense. Overt calcification as in this case is usually seen in psammomatous and meningothelial. Well collaboration between clinician, radiologist, and histopathologist is the key to ensure patient’s recovery and safety